Kyai, Marhabaan, Religiosity and Social Change in Tasikmalaya - Mardani, Dede Aji (Proceeding International Conference on Religion, Science and Education, 2022)
The purpose of this study is to analyze the relationship between marhabaan celebrations with the level of religiosity and massive social change. The method used is sociological anthropology in which researchers are directly involved in the religious celebration of marhabaan. The results of the study showed that the marhabaan celebration that had been carried out had fostered a very strong kinship where the event was a place to exchange ideas and share opinions, chat and control the descendants of each participant. This marhabaan is usually carried out by the Nahdahatul Ulama organization or mass organizations affiliated with it, but not by Muhammadiyah and Persis organizations. The next finding is that marhabaan has formed a moral bond for charity, alms and philanthropy. The role of religious leaders holds the most important key in broadcasting the marhabaan tradition, because the community will follow what the kyai says. However, the level of religiosity, social change and religious observance of the community in formal rituals did not show any changes and improvements. This is evidenced by the crime rate, juvenile delinquency, drugs, poverty that still surrounds the city of Tasikmalaya as well as in the implementation of the five daily prayers, this is because the values contained in the poems and verses of marhabaan are not actualized in everyday life, so that marhabaan is still an annual ritual in the welfare of its congregation for a while not yet at the level of sustainable social change.